Managing Competition Policy and the Digital Markets Act - Klajnšek, Aljanka; Hmelak, Maja (Digital Platforms: Legal And Economic Challenges, 2024)
The paper analyses shortcomings in the management of competition policy in digital markets at the EU level between 2010 and 2024. The paper aims to emphasize the role of the manager of the competition policy at the EU level, the shortcomings of the management, and the efforts to regulate the digital environment, which would help prevent unfair competition. The novelty lies in the approach to the question from a legal, management and information point of view, as well as the perspective of the approach. The research focuses on analysing the shortcomings of the management in the field concerned and the associated infringements of competition rules. Current cases of abuse of dominant market position by major online platforms are presented, along with solutions for the provision of services in digital markets provided by the Digital Markets Act.